Physicochemical Characteristics and Dietary Fiber of Analog Rice from Seaweed (Sargassum sp.) and Beneng Taro Combination - Aditia, Rifki Prayoga; Haryati, Sakinah; Muhede, Aditia Mursyid; Nuryadin, Devi Faustine Elvina (University of Sultan Ageng Tirtayasa, 2023)
Development of analog rice from Sargassum sp. and beneng taro combination is expected to be an alternative food to increase the amount of dietary fiber intake for the community. The aim of this research is to determine the best characteristics of analog rice from Sargassum sp. and beneng taro as a high fiber food. The concentration of added Sargassum sp. seaweed in this study were 0%, 5%, 10%, and 15%. The results showed that a concentration of 15% was the best treatment with a white degree value 1.23%; water absorption capacity 61% and swelling power 59.3%. The chemical characteristics of the best analog rice are 10.14% moisture content; ash content 4.14%; fat content 0.60%; protein content 5.69%; and carbohydrates content 79.44%. The dietary fiber of analog rice is 23.74%.